Principal’s Instructional Leadership in Enhancing Teachers’ Pedagogical Competence at SD Negeri 2 Tulakan - Anita Nadzifah; Bunyamin Bunyamin; Yovitha Yuliejantiningsih (Journal of Educational Sciences, 2026)
This study aims to analyze and describe the instructional leadership of the principal in improving teachers’ pedagogical competence at SD Negeri 2 Tulakan. A qualitative approach was employed to explore in depth the principal’s instructional leadership practices, which include defining the school mission, supervising and evaluating instruction, promoting professional development and maintaining high visibility. Data were collected through in-depth interviews, observations, and document analysis, then analyzed thematically to identify leadership patterns and their contribution to the enhancement of teachers’ pedagogical competence. The findings reveal that the principal has implemented instructional. These practices significantly contribute to the improvement of teachers’ pedagogical competence, although several challenges remain, such as limited resources, resistance from some teachers, and restricted time for instructional supervision. This study recommends the need for continuous leadership training, strengthened coordination between the principal and teachers, and the development of a more effective supervision system to optimize the implementation of instructional leadership in primary schools.